2008
DOI: 10.1136/aim.26.3.149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Manual Acupuncture with Sparrow Pecking on Muscle Blood Flow of Normal and Denervated Hindlimb in Rats

Abstract: Introduction In clinical practice, it has been thought that acupuncture might serve to wash out pain-generating metabolic end-products by improving blood circulation in muscles. We investigated the effects of manual acupuncture (MA) on muscle blood flow (MBF) of normal and denervated hindlimbs in rats. Method Sprague-Dawley rats (n=100) anaesthetised with urethane (1.2g/kg ip) were used. Manual acupuncture with sparrow pecking (SP) at different doses (1, 10 or 30 pecks) was given to the right ventral hindlimb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…However, the increase continues for at least 1 h after MA. 9 Because the present study estimated the MBF at 3 min after MA (early phase), it is possible that PGs are involved in the increase after the early phase. On the other hand, the following systems are independent of NO or PG: (1) several vasodilators such as CGRP, ATP, ADP and adenosine, which directly bind to their respective receptors on vascular smooth muscle cells; and (2) endothelium-derived hyperpolarising factors (EDHF), which are proposed to be potassium ions (K + ), cytochrome P450 metabolites, hydrogen peroxide (H 2 O 2 ) or gap junctions between endothelial cells and smooth muscle cells (myoendothelium gap junction).…”
Section: Mean Arterial Blood Pressure (Map)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the increase continues for at least 1 h after MA. 9 Because the present study estimated the MBF at 3 min after MA (early phase), it is possible that PGs are involved in the increase after the early phase. On the other hand, the following systems are independent of NO or PG: (1) several vasodilators such as CGRP, ATP, ADP and adenosine, which directly bind to their respective receptors on vascular smooth muscle cells; and (2) endothelium-derived hyperpolarising factors (EDHF), which are proposed to be potassium ions (K + ), cytochrome P450 metabolites, hydrogen peroxide (H 2 O 2 ) or gap junctions between endothelial cells and smooth muscle cells (myoendothelium gap junction).…”
Section: Mean Arterial Blood Pressure (Map)mentioning
confidence: 99%
“…However, denervation caused by cutting the sciatic nerve, 9 destruction of the thin sensory nerves caused by capsaicin 7 and topical application of hCGRP [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (a CGRP receptor antagonist) 7 did not completely suppress the MA-induced increase in MBF, suggesting that other vasodilators contribute to this effect. A recent report showed that application of MA using the rotating needle technique locally raised the extracellular concentration of ATP, ADP, AMP or adenosine in mice 3 and humans.…”
Section: Mean Arterial Blood Pressure (Map)mentioning
confidence: 99%
“…Several recent studies 7,158,161,164,[169][170][171] support the use of dry needling in the management of tendinopathy; more specifically, dry needling has been shown to positively influence tendon healing by increasing blood flow via local vasodilation 161,163,164,169 and collagen proliferation. 158,170 It is theorized that the lack of blood flow and subsequent hypoxic environment contributes to 'tendon dysrepair' 172 and leads to the pain and disability associated with chronic tendinopathy.…”
Section: Dry Needling For Tendinopathy Not Just Trpsmentioning
confidence: 99%
“…In our previous studies using radiolabelled microspheres, we have shown that MA significantly increased local MBF in rats. [11][12][13] This increase was observed immediately after denervation, suggesting the possibility of axon reflex participation in the increase. 11 However, the increase was also observed after chronic denervation, although it seemed to be attenuated by it.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] This increase was observed immediately after denervation, suggesting the possibility of axon reflex participation in the increase. 11 However, the increase was also observed after chronic denervation, although it seemed to be attenuated by it. Thus, in our previous study, it was unclear whether axon reflex participated in the increase or not.…”
Section: Introductionmentioning
confidence: 99%